The Ace of Spades: Reverse Takotsubo Cardiomyopathy in the Context of Angiographic Embolization of Recurrent Metastatic Serotonin-Positive Neuroendocrine Tumour of the Pancreas - Ian A. Mazzetti; Michael J. Marcaccio; Odette Boutross-Tadross; Omid Salehian; Catherine Demers (Case Reports in Medicine)
A 62-year-old woman undergoing embolization of recurrent neuroendocrine tumor, positive for serotonin, developed chest pain and bradycardia with lateral ST-segment depression. Cardiac biomarkers were elevated, and echocardiography revealed akinesis of all basal segments with a normally contracting apex. The absence of flow-limiting coronary disease on angiography confirmed the presence of reverse Takotsubo cardiomyopathy. After optimal medical therapy for six weeks, left ventricular function returned to normal. Takotsubo cardiomyopathy has been described across a wide variety of hyperadrenergic states; the description of the reverse-type Takotsubo cardiomyopathy in the setting of embolization of recurrent neuroendocrine with serotonergic positivity tumour is novel.